A new monocomponent xylanase improves performance, ileal digestibility of energy and nutrients, intestinal morphology, and intestinal microbiota in young broilers - Vasanthakumari BL; Gedye KR; Abdollahi MR; Di Benedetto M; Sanchez DG; Wealleans A; Ravindran V (Elsevier Inc. on behalf of Poultry Science Association Inc., 2023)
Supplementation of feed enzymes such as xylanases has been shown to lower intestinal digesta viscosity and improve nutrient digestion thereby resulting in better gut health due to the reduced availability of undigested nutrients for the growth of harmful bacteria. Oligosaccharides produced by xylanase in situ from dietary non-starch polysaccharides with potential prebiotic effects could modulate the gut microbiome. This paper reports the positive effects of a new monocomponent xylanase in improving performance and nutrient digestion and modulating the intestinal microbiota of broilers. A corn-wheat-soybean meal-based diet was formulated and used to develop 3 dietary treatments using different doses (0, 45,000 U/kg and 90,000 U/kg) of the xylanase. A total of 288, one-day-old male broiler (Ross 308) chicks were allocated to 36 cages (12 replicates per treatment and 8 chicks per cage) and offered the experimental diets from d 0 to 21 post-hatch. The data were subjected to ANOVA using the General Linear Models procedure of SAS. The results confirm that supplemental xylanase at both dose levels improved (P < 0.05) broiler performance and nutrient digestibility. Xylanase supplementation had significant (P < 0.05) effects in modulating the intestinal microbiota with a higher relative abundance of commensal bacteria such as Lactobacillus and a lower abundance of potentially non-beneficial bacteria such as E. shigella indicating a prebiotic mode of action.